Amphiphilic water soluble cationic ring opening metathesis copolymer as an antibacterial agent - Islam, Muhammad Nazrul; Aksu, Burak; Guncu, Mehmet; Gallei, Markus; Tulu, Metin; Eren, Tarik (WILEY, 2020)
Bacterial infection is a global problem, especially resistance acquired by bacteria against to antibiotics; there is urgent need for the development of antibiotics. Here, we proposed dendron-grafted polymers via ring opening metathesis polymerization (ROMP) featuring different with tailored hydrophobicity/hydrophilicity and cationic charges. Dendritic oxanorbornene derivatives were synthesized having two and six carbon linkers and their corresponding random and block copolymers were prepared having pendant pyridinium salt moieties via ROMP. In total, 12 different water-soluble dendronized cationic polymers featuring hexyl pyridinium moieties were prepared and investigated. Six carbon linker possessing triple charge density and hexyl pyridinium functionality each repeating unit copolymers exhibited high antibacterial activity against Gram-positive bacteria (S. aureus). However, all the polymers were inactive against Gram-negative bacteria (E. coli). Most of the copolymers are non-hemolytic (>HC (50) = 1,000 mu g/ml). It was also observed that, there is no significant effect between block copolymers and random copolymers keeping hydrophobicity and cationic charge density constant. Zeta potential was measured to investigate the mechanism in solution via the interaction of polymers with S. aureus, while scanning electron microscope (SEM) measurements image confirms damage of the bacterial cell wall after implementation of biocidal polymer.
Keywords: antimicrobial; biocidal; dendron; ROMP; structure-property relationship; ANTIMICROBIAL PEPTIDES; SYNTHETIC MIMICS; CHARGE-DENSITY; POLYMERS; DESIGN; RESISTANCE; DERIVATIVES; SURFACES; NANOPARTICLES; DENDRIMERS; Polymer Science